Oral Educative communication and its relation with the kinetic performance of youngsters or teenagers at handball - belouadeh, chaker (sports creativity, 2025)
he aims of the study were : Helping the trainer (coach) and the trainee to understand the correct ways of positive communication, knowing the impact of the oral communication on learning different kinetic skills and knowing the importance of this type of communication in the training session, We have relied in our study on the descriptive analytical approach because it is the most appropriate for such research, Our research sample included 30 emerging handball players from Bou-Saada team, which is The Questionnaire (Survey). After collecting questionnaire form, we calculated the Iteration of answers for each question then we calculated the percentage of each question depending on this equation, and the most important results were Speaking, Listening and Asking Skill effects of the kinetic performance between the trainee Youngsters and the Coach.